Evaluating the blood Serum Hormones, Cholesterol Levels in Seminiferous Plasma and Certain Semen Parameters in Males with Asthenozoospermia - نورالدين عبدالرضا (Academic Science Journal)
Infertility is a medical condition that afflicts many men around the world and has many and complex causes. It is a malfunction in the male reproductive system. Its causes can be genetic, hormonal or a defect of semen components. This study was included two groups, the infertile (Asthinozoospermia) and the fertile or the control group (Normozoospermia), where each group consisted of 33 men average age (31.57 ± 1.11, 30.93 ± 1.04) respectively. Seminal fluid analysis (SFA) were conducted for them according to the recommendations of the World Health Organization (WHO), and the concentration level of cholesterol in seminal plasma was estimated using ELISA (Enzyme Linked Immuno-Sorbent Assay) and the concentration levels of blood serum hormones (FSH, LH, Prolactin, Testosterone) were estimated using the Chemiluminescence Immunoassay System (CL-900i) device. The study showed great convergence in the average age, BMI, semen volume and semen pH at asthenozoospermia group and Normazoospermia group, without a statistical significant difference (P>0.05). But there was a statistical significant difference (P<0.01) between Asthenozoospermia group and Normozoospermia group at sperm count, Progressive motility %, No-progressive motility % and immotile%. There was also, a significant difference between the two groups in the seminal plasma cholesterol concentration, (P<0.01). While there was no significant difference(P<0.05) between the two groups in the level of serum FSH, LH, Prolactin and Testosterone concentrations.